2007
DOI: 10.2109/jcersj2.115.491
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Absorption Reaction of Li4SiO4 studied by the Rate Theory using Thermogravimetry

Abstract: The CO 2 absorption property of Li 4 SiO 4 was investigated by thermogravimetry. Two kinds of sintered Li 4 SiO 4 samples were prepared at 700? C and 1000? C. The CO 2 absorption rate of the powdered Li 4 SiO 4 samples was measured in 100 vol! CO 2 atmosphere at nine selected temperatures in the 620Ĭ700? C region, and the measured data were discussed by the rate theory. The CO 2 absorption reaction of the Li 4 SiO 4 would be a pseudo first order reaction. For these samples, apparent reaction rate constants k w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…On the basis of the equation (4), the slope corresponds with kPCO 2 , and PCO 2 was fixed as 0.1 MPa in the measurement. According to our previous report, 14) in this study, we also supposed that the CO2 absorption reaction is a pseudo first order reaction until the time which the break point is found at. Thus, apparent rate constant k for all the samples was estimated from the measured slope (kPCO 2 = k × 0.1) at 620, 630, 640, 650, 660, 670, 680, 690, 700°C.…”
Section: Co2 Absorption Measurementmentioning
confidence: 79%
See 3 more Smart Citations
“…On the basis of the equation (4), the slope corresponds with kPCO 2 , and PCO 2 was fixed as 0.1 MPa in the measurement. According to our previous report, 14) in this study, we also supposed that the CO2 absorption reaction is a pseudo first order reaction until the time which the break point is found at. Thus, apparent rate constant k for all the samples was estimated from the measured slope (kPCO 2 = k × 0.1) at 620, 630, 640, 650, 660, 670, 680, 690, 700°C.…”
Section: Co2 Absorption Measurementmentioning
confidence: 79%
“…5, the reaction lnk = lnA mechanism seems to change around 670°C because the lnk values abruptly increase around 670°C. In our previous report, 14) we discussed that the change in the k (or lnk) values seems to depend ln - …”
Section: Co2 Absorption Measurementmentioning
confidence: 90%
See 2 more Smart Citations
“…8,9 Among these technologies, capture is the area for which effective sorbent materials must be developed. 15,17,18,23,[25][26][27][28][29] As for Li 2 SiO 3 , experimental results showed the kinetics of its CO 2 capture reaction are also too slow, and hence it is not a good candidate for a CO 2 capture technology. Recent experimental investigations found that alkali metal silicates and zirconates are good candidates as solid sorbents for CO 2 capture in terms of large CO 2 sorption capacity, infinite CO 2 /N 2 or CO 2 /H 2 selectivity, good reversibility, and high operating temperatures.…”
mentioning
confidence: 99%